The resistance of wood fibers-poly(vinyl chloride) composites to UV-irradiation - Kaczmarek, H.; Zielińska, A.; Sionkowski, G.; Bajer, K.; Stasiek, A.; Dzwonkowski, J. (Polimery, 2022)
Wood fibers-poly(vinyl chloride) (WF-PVC) composite and pure poly(vinyl chloride) samples, prepared by extrusion, were exposed to short wavelength UV-irradiation (?=253.7nm). Scanning Electron Microscopy (SEM) micrographs shows heterogeneity of WF-PVC composite but the effect of UV-irradiation on surface morphology of sample is negligible. The course of photochemical reactions occurring in samples studied has been monitored by attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy. The results obtained indicate the better photochemical stability of WF-PVC comparing to virgin PVC.